The importance of therapeutic drug monitoring (TDM) for parenteral busulfan dosing in conditioning regimen for hematopoietic stem cell transplantation (HSCT) in children - Tesfaye, Hundie; Branova, Romana; Klapkova, Eva; Prusa, Richard; Janeckova, Daniela; Riha, Petr; Sedlacek, Petr; Keslova, Petra; Malis, Josef (Annals of transplantation, 2014)
BACKGROUND: Series of observations indicate PK/PD variability challenging the accuracy of the body-weight based busulfan (Bu) dosing schedule for (HSCT) conditioning therapy. The purpose of this communication is to describe the frequency of dose changes in initially body-weight-based fixed IV Bu dose and to emphasize the importance of TDM. MATERIAL AND METHODS: Sixty-two children (ages 2 months-18 years) were treated with IV busulfan doses based on body weight for myeloablation. TDM utilizing a limited sample strategy (trough concentration immediately before the 5th dose, followed by samples immediately after the end of the 2-h infusion peak, 4 h, and 6 h from initiation of the infusion) was performed in 46 of 62 subjects. Busulfan concentrations were determined by high-performance liquid chromatography (HPLC). AUC was calculated according to the trapezoidal rule. RESULTS: We observed trough levels of 25-1244 µg/L, peak levels of 849-4586 µg/L, and AUC of 2225-12818 µg/L·h following body weight-based high-dose busulfan. The doses were changed in 54% of cases. AUC in 5 of 9 patients with VOD were within target, in 3 patients AUS was higher, and in 1 patient AUC was lower. One of the 2 patients with neurotoxicity had higher AUC. Engraftment was 100%, but relapse occurred in 25% of cases. CONCLUSIONS: Our results demonstrate that even with IV busulfan, intra-individual PK/PD variability is challenging. Although AUC does not necessarily correspond with outcomes (due to the role of other factors the fact that doses were changed in 54% of cases underlines the importance of TDM.
Keywords: Infusions, Intravenous; lidé; mladiství; dithiokarb; adjuvancia imunologická; Transplantation Conditioning; Infant; busulfan; dítě; Myeloablative Agonists; vztah mezi dávkou a účinkem léčiva; Chromatography, High Pressure Liquid; Adolescent; Humans; myeloablativní agonisté; Dose-Response Relationship, Drug; intravenózní infuze; Hematopoietic Stem Cell Transplantation; předškolní dítě; Child, Preschool; vysokoúčinná kapalinová chromatografie; příprava pacienta k transplantaci; Ditiocarb; monitorování léčiv; transplantace hematopoetických kmenových buněk; Drug Monitoring; Adjuvants, Immunologic; tělesná hmotnost; Busulfan; Child; Body Weight; kojenec